2007
DOI: 10.1093/nar/gkm863
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a novel non-coding mitochondrial RNA in human proliferating cells

Abstract: Previously, we reported the presence in mouse cells of a mitochondrial RNA which contains an inverted repeat (IR) of 121 nucleotides (nt) covalently linked to the 5′ end of the mitochondrial 16S RNA (16S mtrRNA). Here, we report the structure of an equivalent transcript of 2374 nt which is over-expressed in human proliferating cells but not in resting cells. The transcript contains a hairpin structure comprising an IR of 815 nt linked to the 5′ end of the 16S mtrRNA and forming a long double-stranded structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
137
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(157 citation statements)
references
References 56 publications
15
137
0
Order By: Relevance
“…1B, Right). A similar expression pattern was obtained with 8 additional tumor cell lines (2). The normal proliferating cells HUVEC, HFK, and HUTEC also express this transcript (Fig.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…1B, Right). A similar expression pattern was obtained with 8 additional tumor cell lines (2). The normal proliferating cells HUVEC, HFK, and HUTEC also express this transcript (Fig.…”
Section: Resultssupporting
confidence: 80%
“…R ecently, we described a novel human mitochondrial transcript of 2,374 nt that contains a long inverted repeat (IR) linked to the 5Ј end of the 16S mitochondrial rRNA (16S mtrRNA) (1, 2), which we designated noncoding mitochondrial RNA or ncmtRNA (2). The IR generates a stem-loop structure with an 820-bp doublestranded region and a 40-nt loop (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Later the same workers demonstrated that human cells contain a transcript of 2374 nt with similar structural features to the mouse mtRNA. This transcript contained a stem-loop structure with an 820-bp double-stranded region and a 40-nt loop, and that it was expressed in human proliferating cells but not in resting cells, suggesting that this ncmtRNA may play a role in cell proliferation [73]. Recently, Burzio et al [74] reported that in addition to this transcript, normal human proliferating cells in culture expressed two ncmtRNA transcripts, sense ncmtRNA (SncmtRNA) and antisense ncmtRNA (ASncmtRNA).…”
Section: Noncoding Mitochondrial Rnasmentioning
confidence: 99%